Pemberdayaan Ibu Rumah Tangga Melalui Edukasi Investasi Syariah Berbasis Sektor Riil di Kecamatan Kedungwaru Kabupaten Tulungagung - Meirini, Dianita; Khoiriawati, Novi; Fitriasari, Amanda (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance participants’ Islamic financial literacy, bookkeeping skills, and awareness of the importance of ideal budget allocation in accordance with the Financial Services Authority (OJK) standards, enabling housewives to manage family income more balancedly and with a future-oriented perspective. The program was implemented using a participatory education approach, and its outcomes were evaluated through pre-test and post-test analyses. The results indicated an improvement in participants’ understanding of family financial planning based on Islamic principles, particularly in incorporating components such as investments, emergency savings, and zakat into household budgets. Furthermore, participants became capable of preparing more proportional budgets and understanding ideal expenditure allocations, including a recommended minimum investment of 5%–15% of income. Investment interest increased significantly, with 89% of participants expressing willingness to allocate a portion of their income for investment, primarily in gold, bank savings, land, and deposits. Overall, the program was deemed successful, as evidenced by full participant engagement and measurable improvements in financial literacy and investment interest.